Hepatic SREBP-2 and cholesterol biosynthesis are regulated by FoxO3 and Sirt6 - Tao, Rongya (The American Society for Biochemistry and Molecular Biology, 2013)
Cholesterol homeostasis is crucial for cellular function and organismal health. The key regulator for the cholesterol biosynthesis is sterol-regulatory element binding protein (SREBP)-2. The biochemical process and physiological function of SREBP-2 have been well characterized; however, it is not clear how this gene is epigenetically regulated. Here we have identified sirtuin (Sirt)6 as a critical factor for Srebp2 gene regulation. Hepatic deficiency of Sirt6 in mice leads to elevated cholesterol levels. On the mechanistic level, Sirt6 is recruited by forkhead box O (FoxO)3 to the Srebp2 gene promoter where Sirt6 deacetylates histone H3 at lysines 9 and 56, thereby promoting a repressive chromatin state. Remarkably, Sirt6 or FoxO3 overexpression improves hypercholesterolemia in diet-induced or genetically obese mice. In summary, our data suggest an important role of hepatic Sirt6 and FoxO3 in the regulation of cholesterol homeostasis.